I Cannot Read Your Eye Expression: Suicide Attempters Have Difficulties in Interpreting Complex Social Emotions - Ferrer, Inés; Alacreu-Crespo, Adrián; Salvador, Alicia; Genty, Catherine; Dubois, Jonathan; Sénèque, Maude; Courtet, Philippe; Olié, Emilie (Frontiers in Psychiatry, 2020)
Background: The ability to differentiate emotions in social contexts is important for dealing with challenging social situations. Suicide attempters show some difficulties in emotion recognition that may result in hypersensitivity to social stress. However, other studies on the recognition of social complex emotions found that suicide attempters have similar performances as depressed non-attempters. Objectives: To investigate differences in social emotion recognition in patients with current Major Depressive Episode (MDE) with and without history of suicide attempt. Methods: 210 patients with MDE were recruited among whom 115 had lifetime history of suicide attempt (suicide attempters, SA) and 95 did not (affective controls, AC). Recognition of complex social emotions was assessed using the Reading the Mind in the Eyes Test (RMET). Emotions were separated in three valence categories: positive, negative, and neutral. Verbal intelligence quotient (IQ) and attention were measured with the National Adult Reading Task (NART) and the d2 test, respectively. Results: Mixed logistic regression models adjusted for sex, lifetime bipolar disorder, verbal IQ and attention showed that the RMET performance for neutral emotions was worse in the SA than AC group (OR = .87 [.75, .99]). Furthermore, when violent/serious SA were compared to non-violent/non-serious SA and AC, the RMET neutral valence category showed a trend for group factor (p < .059) and RMET scores were lower in the violent/serious SA than AC group (OR = .79 [.64, .96]). Conclusion: Recognition of neutral emotions is poor in SA and this may complicate their daily life. Interventions to improve the understanding of complex emotions may be helpful to prevent suicidal risk in patients with depression.